Global Poverty and Inequality: Change and Continuity in Late Development. Issue 2 (8th March 2019) - Sumner, Andy
ABSTRACT: This contribution assesses the 'converging divergence' thesis that global inequality is falling and national inequality is rising. The article argues that falling global inequality is primarily due to China's development and that national inequality has risen in some developing countries and fallen in others. In light of the dominance of China's development in the global picture, questions arise as to what has changed and what has not changed outside of China. A set of changes and continuities is presented. It is then argued that these changes and continuities provide for the contemporary relevance an older conceptual lens — that of 'late development'.